2017
DOI: 10.4236/jss.2017.57021
|View full text |Cite
|
Sign up to set email alerts
|

House Price, Ownership Type and Firm Innovation

Abstract: This paper chooses the data of high-tech enterprises in China from 2007 to 2014, and investigates the impact of house price on firm innovation. The conclusion is that the house prices are significantly negatively related to the firm innovation, and compared to the prices of the operating buildings and the office buildings, the negative effect of the increasing price of commercial buildings as a whole, residential buildings (large categories), or other commercial building in the similar category is more signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…The empirical findings support the hypotheses proposed in this paper, demonstrating that rising housing prices have a significant positive effect on corporate green innovation. This finding contradicts previous studies that suggest rising housing prices hinder enterprise innovation (Wang, 2014(Wang, , 2017Zhao et al, 2016Zhao et al, , 2019, while aligning with research that highlights the positive impact of urban housing prices on city and enterprise innovation (Chaney et al, 2012;Wang, 2020;Lin et al, 2021). Therefore, the empirical results provided in this study enhance the understanding of the influence of housing prices on firm innovation.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The empirical findings support the hypotheses proposed in this paper, demonstrating that rising housing prices have a significant positive effect on corporate green innovation. This finding contradicts previous studies that suggest rising housing prices hinder enterprise innovation (Wang, 2014(Wang, , 2017Zhao et al, 2016Zhao et al, , 2019, while aligning with research that highlights the positive impact of urban housing prices on city and enterprise innovation (Chaney et al, 2012;Wang, 2020;Lin et al, 2021). Therefore, the empirical results provided in this study enhance the understanding of the influence of housing prices on firm innovation.…”
Section: Discussioncontrasting
confidence: 99%
“…Secondly, this paper examines the differential impact of housing prices on corporate green innovation based on variations in enterprise characteristics and regional differences. Previous studies have suggested that the inhibiting effect of housing prices on enterprise innovation is more pronounced in state-owned enterprises (Wang, 2017; Zhao et al ., 2019). However, the findings of this paper contradict this conclusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations